Fertilizer sowing simulation of a variable-rate fertilizer applicator based on EDEM. Issue 17 (2018) - Yang, Liwei; Chen, Longsheng; Zhang, Junyi; Liu, Haojie; Sun, Zichun; Sun, Hong; Zheng, Lihua
Abstract: The simulation for a variable fertilization machine could help to show the fertilizing result and provide theoretical guidance in reality machine operation. EDEM (Extended distinct element method) which is a general-purpose software for simulating and analyzing particle system is widely used in simulation experiments of fertilizing machines. In order to optimal design of a variable-rate fertilizer machine. This paper uses EDEM to simulate the spread of three kinds of fertilizers which are potassium chloride, potassium sulfate and urea, commonly used in agriculture, by a centrifugal disc type variable-rate fertilizer applicator. After analysis, the variation coefficients of the lateral homogeneity of the three fertilizers are 43.34%, 26.26% and 39.21%, respectively. The result shows that simulation effect of these three fertilizers is not up to standard, and further research is needed to improve the performance of the fertilizer machine.